Fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium as well as structure regulation and control method and application method of fluorine-containing polymer microsphere adsorbent

The fluorine-containing polymer microsphere adsorbent prepared by emulsion polymerization uses 2-(perfluorooctyl)ethyl methacrylate as the functional monomer to solve the problems of poor selectivity and low adsorption capacity of existing lithium adsorbents. , achieving efficient and economical lithium ion adsorption effect.

CN119350704AActive Publication Date: 2025-01-24常州中源技术股份有限公司

Patent Information

Application Number
CN202411900087.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing lithium adsorbents have poor selectivity, low adsorption capacity, high preparation cost and complex preparation process, making it difficult to meet the needs of lithium resource recycling and environmental protection.

Method used

Use 2- (full fluorinel) ethyl methyl acrylic as a functional monomer, prepare a fluorine polymer microsphere adsorption agent through lotion polymerization, optimize monomer ratio, choose the appropriate emulsifier and emulsified process, control Stirring conditions and temperature, adjust the amount and type of dotter agent to form a microsphere adsorption agent with high selectivity and adsorption capacity.

Benefits of technology

The high selectivity and high adsorption capacity of lithium ions is realized, the preparation cost is reduced, the preparation process is simplified, and the lithium ions can be effectively absorbed in an environment containing a large number of competitive ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350704A_ABST
    Figure CN119350704A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of lithium adsorbents, in particular to a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium as well as a structure regulation and control method and an application method thereof, and solves the technical problems of poor selectivity, low adsorption capacity, high preparation cost and complex preparation process of an existing lithium adsorbent. The fluorine-containing polymer microsphere adsorbent material based on the emulsion polymerization method is synthesized, operation is easy, cost is low, synthesis efficiency is high, large-scale preparation can be achieved, and high selectivity and adsorption capacity are achieved. The adsorbent material can efficiently and selectively adsorb lithium ions in lithium-containing wastewater containing a large number of coexisting monovalent and high-valent competitive ions, the adsorbability of the adsorbent material to the lithium ions is far better than that of the adsorbent material to ions such as sodium, potassium, cobalt, manganese and the like, and the adsorption capacity of the adsorbent material to the lithium ions can reach 38.5 mg / g at most.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium adsorbent preparation, and in particular to a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium, and a structure control method and an application method thereof. Background Art

[0002] Lithium is known as "high-energy metal" and "white oil" of the new era. It is a strategic metal that promotes the development of the new energy industry. As a lightweight, high-energy-density metal element, lithium is widely used in batteries, ceramics, glass, and nuclear industries. In recent years, the rapid commercialization of new energy vehicles and portable electronic devices has led to a rapid expansion of the lithium battery market, a sharp increase in demand for lithium resources, and possible risks in the supply of lithium resources. At the same time, according to the scrap cycle of power batteries, a wave of power battery retirement is currently underway. If these retired power lithium batteries are not handled properly, on the one hand, lithium resources will be wasted, and on the other hand, substances such as nickel, cobalt, and manganese in the electrode materials will cause secondary pollution to the environment. Therefore, selective recovery of lithium from lithium-containing waste liquid is crucial to the supply of lithium resources and the reduction of environmental pollution.

[0003] However, the composition of lithium-containing waste liquid is relatively complex, containing a large number of coexisting monovalent and high-valent metal competitive ions. The adsorption method is a lithium recovery method with simple process, high efficiency, strong selectivity, low cost and environmental friendliness. It uses lithium adsorbents to adsorb lithium from lithium-containing waste liquid, and then uses certain solvents to desorb, thereby recovering lithium as a resource. Adsorbents are the core of lithium recovery by adsorption. Common lithium adsorbents mainly include inorganic, organic and composite adsorbents. Inorganic adsorbents include metal-based adsorbents and natural mineral-based adsorbents. Metal-based adsorbents are basically composed of aluminum-based, manganese-based and titanium-based adsorbents. Aluminum-based adsorbents have high technical maturity and the greatest potential in industrial applications, but their selectivity for lithium is not ideal; manganese-based materials have good lithium adsorption performance, but the dissolution of manganese affects their long-term stable application; titanium-based adsorbents have high adsorption efficiency, high lithium selectivity, good cycle stability and acid and alkali resistance, but the cost is relatively high and not suitable for large-scale industrial applications. Natural mineral-based adsorbents have the advantages of excellent adsorption performance and sustainable utilization, but their scope of application is limited and impurities may exist. Composite adsorbents combine the advantages of multiple adsorbents and have higher adsorption efficiency, but the preparation process may be more complicated and the cost is higher. Organic adsorbents, such as crown ethers and polymer ion exchange resins, are difficult to be widely used due to their complex synthesis process.

[0004] Emulsion polymerization is a simple, low-cost, high-efficiency and controllable polymerization method. The morphology, particle size, number and size of chambers of microsphere adsorbents can be freely designed, and large-scale preparation is easy to achieve, which has broad application prospects. Therefore, how to design and prepare microsphere adsorbent materials with stable structure and performance, high adsorption capacity, high selectivity, and large-scale preparation through emulsion polymerization has become a hot topic and difficulty in current research.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The first technical problem to be solved by the present invention is to provide a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium, so as to solve the technical problems of poor selectivity, low adsorption capacity, high preparation cost and complex preparation process of existing lithium adsorbents.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: The fluorine-containing polymer microsphere adsorbent uses 2-(perfluorooctyl)ethyl methacrylate as a functional monomer and is prepared based on an emulsion polymerization method; the emulsion polymerization method uses an emulsion as a reaction medium and converts the monomer into polymer microspheres through a polymerization reaction. Compared with the preparation method of traditional adsorbent materials, the emulsion polymerization method has the advantages of simple operation, mild reaction conditions, large-scale production, and the ability to regulate the microsphere structure.

[0008] The particle size of the fluorinated polymer microsphere adsorbent is 12-17 μm; the pore size of the fluorinated polymer microsphere adsorbent is 50-200 nm, and the specific surface area is 100-300 m² / g. The perfluorooctyl group provides adsorption sites, which attract lithium ions. The microporous structure allows the microsphere adsorbent to adsorb lithium ions to ensure that lithium ions can pass smoothly and combine with the adsorption sites. The molecular formula of 2-(perfluorooctyl)ethyl methacrylate is C 14 H9F 17 O2, molecular weight is 532.19. This structure makes it a special fluorinated acrylate monomer. Its structure contains a methacrylate group and a perfluorooctyl ethyl group. The perfluorooctyl ethyl group is connected by a perfluorooctyl group and an ethyl group. The perfluorooctyl ethyl group itself has low surface energy, hydrophobic and oleophobic properties, which makes 2-(perfluorooctyl) ethyl methacrylate less soluble in water and more difficult to emulsify. It is necessary to select a suitable emulsifier and emulsification process to ensure the stability of the emulsion system.

[0009] The present invention can effectively adjust the structure of microspheres on the basis of emulsion polymerization by optimizing monomer ratio, selecting suitable emulsifier and emulsification process, controlling stirring conditions, accurately controlling temperature, and adjusting the amount and type of initiator, so as to form a microsphere adsorbent with uniform structure and obtain the most satisfactory microporous structure, thereby ensuring the selective adsorption effect of lithium ions.

[0010] The second technical problem to be solved by the present invention is to provide a method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium, and to optimize the microporous structure of the fluorinated polymer microsphere adsorbent by finely adjusting the preparation parameters to achieve optimal selective lithium adsorption performance.

[0011] In order to achieve the above object, the technical solution adopted by the present invention is: A method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium, which is used to prepare the fluorinated polymer microsphere adsorbent, comprises the following steps: S1 determines the preparation method and sets initial parameters to carry out emulsion polymerization; Preferably, in step S1, the preparation method comprises the following steps: S11: adding an emulsifier to deionized water to obtain a uniformly dispersed aqueous solution; dissolving 2-(perfluorooctyl)ethyl methacrylate, ethylene glycol dimethacrylate, methacrylic acid, and azobisisobutyronitrile in chloroform to obtain a uniformly dispersed oil solution; slowly dropping the oil solution into the aqueous solution under high-speed stirring to form a stable milky white oil-in-water emulsion; Preferably, step S11 includes the following steps: S111: Add deionized water and emulsifier into a three-necked flask, stir and mix evenly, and then perform ultrasonic treatment for 3-5 min to obtain a uniformly dispersed aqueous solution; S112: 2-(Perfluorooctyl)ethyl methacrylate, ethylene glycol dimethacrylate, methacrylic acid, and azobisisobutyronitrile were dissolved in chloroform, stirred and mixed evenly, and then ultrasonically treated for 3 to 5 minutes to obtain a uniformly dispersed oil phase solution; S113: placing the three-necked flask in step S111 on a magnetic stirrer and stirring at a speed of 1200-1500 rpm, and then slowly dripping the oil phase solution obtained in step S12 into the three-necked flask with a pipette, and continuing emulsification for 8-10 minutes after the dripping is completed to obtain a stable milky white oil-in-water emulsion; Preferably, the emulsifier is sodium dodecyl sulfate; the mass ratio of the emulsifier to deionized water is 1-2:800; this ensures that the emulsifier is fully dispersed in the deionized water to form a stable aqueous solution. The amount of the emulsifier is sufficient to wrap the oil droplets to prevent them from agglomerating, while not too much to cause the system to be too viscous and affect the emulsification effect.

[0012] Preferably, the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate, the ethylene glycol dimethacrylate and the methacrylic acid is 0.2~0.6:1.82~2.82:1; 2-(perfluorooctyl)ethyl methacrylate is used as a functional monomer to introduce fluorine atoms to improve the adsorption performance of the material. Methacrylic acid is used as a comonomer to adjust the hydrophilicity and ion exchange properties of the polymer, and ethylene glycol dimethacrylate is used as a cross-linking agent to improve the mechanical strength and stability of the microspheres, but too much may cause the microspheres to be too dense, affecting the adsorption performance. The present invention can obtain the most satisfactory microporous structure by fitting and adjusting the parameters under the limitation of the above ratio to achieve the best adsorption effect on lithium ions.

[0013] The amount of methacrylic acid in the chloroform is 33.33-50 g / L; that is, the volume ratio of the mass of methacrylic acid to chloroform is 1 g:(20 mL-30 mL); the appropriate concentration of methacrylic acid in the oil phase solution is ensured, which is neither too diluted nor too thick, and is conducive to its uniform distribution and effective copolymerization in the polymerization reaction.

[0014] The amount of azobisisobutyronitrile in chloroform is 3.33-4 g / L; that is, the mass ratio of azobisisobutyronitrile to chloroform is 1 g:(250 mL-300 mL); as an initiator, the concentration of azobisisobutyronitrile has an important influence on the rate and extent of the polymerization reaction. This range ensures an appropriate initiator concentration, so that the polymerization reaction can proceed smoothly, while avoiding excessive polymerization and overheating caused by too much initiator.

[0015] The volume ratio of chloroform to deionized water is 1:2-3. This ratio helps to form a stable water-in-oil emulsion. Chloroform is used as an oil phase solvent, and its volume is moderate relative to the water phase, which not only ensures that the oil phase is fully dispersed in the water phase, but also avoids the emulsion being too thin or viscous.

[0016] S12: The three-necked flask in step S11 is sealed with a rubber stopper, one end is connected to an oil seal, and the other end is connected to a nitrogen source, and nitrogen is continuously introduced for 8-10 min to remove oxygen in the system and prevent the occurrence of oxidation reaction, and then placed in an oil bath at 70-80 °C and reacted at a speed of 300-500 rpm for 10-12 h to obtain a polymer microsphere mixed solution; S13: After the reaction is completed, the polymer microspheres are recovered by centrifugation, washed with deionized water and ethanol for multiple times, and dried to obtain dry microspheres; Preferably, in step S13, the polymer microspheres are recovered by centrifugation, washed three times with deionized water, and then washed three times with ethanol to remove impurities such as unreacted monomers, emulsifiers and solvents to obtain a product, and then the washed microspheres are dried in a vacuum oven to constant weight; when washing the polymer microspheres, the amount of deionized water is 33.33~40 g / L; the amount of ethanol is 33.33~40 g / L, that is, the volume ratio of the mass of the polymer microspheres to deionized water or ethanol is 1g:(25mL~30mL), which helps to obtain pure polymer microspheres.

[0017] S14: Use ethanol and ethyl acetate solutions to exchange solvents on the dried microspheres respectively and then dry them to obtain a fluorinated polymer microsphere adsorbent material. Specifically, the dried microspheres are placed in a selected solvent, and the solvent is fully infiltrated into the interior of the microspheres by stirring or ultrasonic treatment to exchange with the residual solvent and impurities. The number of exchanges and the time of each exchange need to be optimized according to the adsorption performance of the microspheres and the required degree of structural regulation. The main purpose of solvent exchange is to further remove the residual solvent and impurities in the microspheres, thereby achieving the purpose of micropore regulation. The residual solvent here refers to the residual solvent that has not been completely removed during the polymerization reaction or washing process, which complements the S13 step to ensure the purity and performance of the final fluorinated polymer microsphere adsorbent material. After the solvent exchange is completed, the microspheres are dried to remove the residual exchange solvent and fix the new structure of the microspheres.

[0018] Preferably, in steps S13 and S14, drying the microspheres includes placing the microspheres in a vacuum drying oven, drying them at a constant temperature of 40 to 50° C. for 24 to 25 h, and cooling them to room temperature to obtain dried microspheres.

[0019] S2 measured the pore size and specific surface area of ​​the obtained microspheres; specifically, the morphology of the microspheres was characterized by scanning electron microscopy (SEM) to observe their size, shape and distribution uniformity, and the chemical structure of the microspheres was analyzed by infrared spectroscopy (IR) to confirm the successful introduction of functional monomers and comonomers and the formation of cross-linked structures. The pore size and specific surface area were measured by gas adsorption method.

[0020] S3 adjusts a single parameter, conducts multiple experiments, and records the results of each experiment; S4 fits the empirical formula according to the experimental data and adjusts the parameters according to the fit; Preferably, in step S4, the experimental data is imported into statistical analysis software for linear regression analysis to fit an empirical formula for pore size and specific surface area; S5: repeat the above steps S1 to S4 until a satisfactory microporous structure is obtained to obtain a fluorine-containing polymer microsphere adsorbent.

[0021] Furthermore, in step S5, steps S1 to S4 are repeated, the experimental parameters are gradually adjusted, verification experiments are performed, and the preparation process is iteratively optimized to obtain a fluorine-containing polymer microsphere adsorbent with a satisfactory microporous structure.

[0022] The third technical problem to be solved by the present invention is to provide an application method of a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium, and add the fluorine-containing polymer microsphere adsorbent to lithium-containing wastewater to selectively adsorb lithium ions.

[0023] In order to achieve the above object, the technical solution adopted by the present invention is: A method for applying a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium comprises adding the fluorine-containing polymer microsphere adsorbent into lithium-containing wastewater to selectively adsorb lithium ions, and reacting at a constant temperature under stirring conditions, thereby achieving specific targeted recognition and ultra-high capacity adsorption of lithium ions.

[0024] Furthermore, the amount of the fluorine-containing polymer microsphere adsorbent added to the wastewater is 0.1-2 g / L, the reaction temperature is 25° C., the reaction time is 24 h, and the stirring speed is 180 rpm.

[0025] The beneficial effects of the present invention are: (1) The functional monomer used in the method of the present invention is 2-(perfluorooctyl)ethyl methacrylate. 2-(Perfluorooctyl)ethyl methacrylate contains abundant fluorine elements and can provide more adsorption sites that can be stably combined with lithium ions. Through theoretical calculation and analysis of the interaction between fluorine elements and other monovalent metals, fluorine and lithium have the lowest binding energy, which indicates that fluorine-containing functional monomers will preferentially bind to lithium ions and thus have good selectivity; secondly, the synthesis of microsphere adsorbent materials by emulsion polymerization has been verified to be reasonable and feasible over a long period of time; finally, compared with other fluorine-containing functional monomers (2-(perfluorohexyl)ethyl methacrylate and 2-(perfluorodecyl)ethyl methacrylate), 2-(perfluorooctyl)ethyl methacrylate has the advantages of suitable boiling point reaction and cheaper price, so 2-(perfluorooctyl)ethyl methacrylate is selected as the reaction monomer.

[0026] (2) The present invention synthesizes a fluorine-containing polymer microsphere adsorbent material based on emulsion polymerization, which is simple to operate, low in cost, high in synthesis efficiency, can be prepared on a large scale, and has high selectivity and adsorption capacity for lithium ions. The adsorbent material of the present invention can efficiently and selectively adsorb lithium ions in lithium-containing wastewater containing a large number of monovalent and high-valent competitive ions. The adsorption of lithium ions is much better than the adsorption of sodium, potassium, cobalt, manganese and other ions. The adsorption capacity of lithium ions can reach up to 38.5 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a scanning electron microscope image of a fluorine-containing polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1; Figure 2 Physical picture of the stable oil-in-water emulsion prepared in Experiment 1, Fluorescence microscopy picture of the emulsion droplets stained with Nile red; Figure 3 is the infrared spectrum; Figure 4 This is a graph showing the nitrogen adsorption and desorption curves of a fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1. Figure 5 This is the isothermal adsorption curve of the fluorine-containing polymer microsphere adsorbent material prepared by emulsion polymerization method in experiment 1; Figure 6 This is a kinetic adsorption curve of a fluorine-containing polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1; Figure 7 To test the selective adsorption capacity of fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization for lithium ions in a monovalent metal mixed solution; Figure 8 This study was conducted to test the selective adsorption capacity of a fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization for lithium ions in a high-valent metal mixed solution. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0031] A method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium, which is used to prepare the fluorinated polymer microsphere adsorbent, comprises the following steps: S1 determines the preparation method and sets initial parameters, including the type of emulsifier, the mass ratio of the emulsifier to deionized water, the molar ratio of each reactant, the reaction temperature, the reaction time, etc., to perform an emulsion polymerization reaction; Specific implementation method 1: This implementation method is a method for preparing a fluorine-containing polymer microsphere adsorbent based on an emulsion polymerization method, which is specifically carried out in the following steps: S11. ①. Add deionized water and an emulsifier into a three-necked flask, stir and mix well, and then ultrasonically treat for 3 to 5 minutes to obtain a uniformly dispersed aqueous solution; the emulsifier is sodium dodecyl sulfate; the mass ratio of the emulsifier to deionized water is (1 to 2): 800; ②, dissolve 2-(perfluorooctyl) ethyl methacrylate, ethylene glycol dimethacrylate, methacrylic acid, and azobisisobutyronitrile in chloroform, stir and mix evenly, and then ultrasonically treat for 3-5 min to obtain a uniformly dispersed oil phase solution; wherein the mass ratio of methacrylic acid to the volume ratio of chloroform is 1 g:(20 mL-30 mL); the molar ratio of 2-(perfluorooctyl) ethyl methacrylate to methacrylic acid is (0.2-0.6):1; the molar ratio of ethylene glycol dimethacrylate to methacrylic acid is (1.82-2.82):1; the mass ratio of azobisisobutyronitrile to the volume ratio of chloroform is 1 g:(250 mL-300 mL); the volume ratio of chloroform to deionized water is 1:(2-3); ③. Place the three-necked flask in step ① on a magnetic stirrer and stir at a speed of 1200-1500 rpm, then slowly drip the oil phase solution obtained in step ② into the three-necked flask with a pipette, and continue emulsification for 8-10 min after the addition is completed to obtain a stable milky white oil-in-water emulsion; S12, the three-necked flask in step S11 is sealed with a rubber stopper, one end is connected to an oil seal, and the other end is connected to a nitrogen source, and nitrogen is continuously introduced for 8-10 min, and then placed in a 70-80 °C oil bath pot at a speed of 300-500 rpm for 10-12 h to obtain a polymer microsphere mixed solution; S13. After the reaction is completed, the polymer microspheres are recovered by centrifugation, washed three times with deionized water, and then washed three times with ethanol to obtain a product, and then the washed microspheres are dried in a vacuum oven to constant weight to obtain dry microspheres; the mass ratio of the polymer microspheres to the volume of deionized water is 1g:(25mL~30mL); the mass ratio of the polymer microspheres to the volume of ethanol is 1g:(25mL~30mL); S14: using ethanol and ethyl acetate solutions to perform solvent exchange on the dried microspheres respectively and then drying them to obtain a fluorine-containing polymer microsphere adsorbent material.

[0032] Preferably, in steps S13 and S14, drying the microspheres includes placing the microspheres in a vacuum drying oven, drying them at a constant temperature of 40 to 50° C. for 24 to 25 h, and cooling them to room temperature to obtain a fluorine-containing polymer microsphere adsorbent material.

[0033] S2 measured the pore size and specific surface area of ​​the microspheres; S3 adjusts a single parameter, conducts multiple experiments, and records the results of each experiment; S4 fits the empirical formula according to the experimental data and adjusts the parameters according to the fit; Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the volume ratio of chloroform to deionized water in step S1 is 1:3. Other aspects are the same as the specific embodiment 1.

[0034] Specific embodiment 3: This embodiment differs from specific embodiment 2 in that: in step S1, deionized water and emulsifier are added to a three-necked flask, stirred and mixed evenly, and then ultrasonically treated for 5 minutes to obtain a uniformly dispersed aqueous phase solution. Others are the same as specific embodiment 1 or 2.

[0035] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that: in step S1, 2-(perfluorooctyl)ethyl methacrylate, ethylene glycol dimethacrylate, methacrylic acid, and azobisisobutyronitrile are dissolved in chloroform, stirred and mixed evenly, and then ultrasonically treated for 5 minutes to obtain a uniformly dispersed oil phase solution. The rest is the same as one of specific embodiments 1 to 3.

[0036] Specific embodiment 5: This embodiment differs from specific embodiment 4 in that: in step S1, the three-necked flask is placed on a magnetic stirrer and stirred at a speed of 1500 rpm, and then the oil phase solution obtained in step S2 is slowly dripped into the three-necked flask with a pipette, and after the dripping is completed, the emulsification is continued for 10 minutes to obtain a stable milky white oil-in-water emulsion. The rest is the same as one of specific embodiments 1 to 4.

[0037] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that: in step S2, nitrogen is continuously introduced into the water-in-oil emulsion obtained in step S1 for 10 min, and then placed in a 70°C oil bath at a speed of 500 rpm for 10 h to obtain a polymer microsphere mixed solution. The rest is the same as one of specific embodiments 1 to 5.

[0038] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that: in step S3, the product obtained in step S2 is placed in a vacuum drying oven, dried at a constant temperature of 40°C for 24 hours, and cooled to room temperature to obtain a fluorine-containing polymer microsphere adsorbent material based on emulsion polymerization. The rest is the same as specific embodiment 6.

[0039] S5: repeat the above steps S1 to S4 until a satisfactory microporous structure is obtained to obtain a fluorine-containing polymer microsphere adsorbent.

[0040] Specifically, the present invention is verified by the following test: Experiment 1: This embodiment is a method for preparing a fluorine-containing polymer microsphere adsorbent based on an emulsion polymerization method, which is specifically carried out in the following steps: S11. ①. Add 60 mL of deionized water and 0.150 g of emulsifier into a three-necked flask, stir and mix evenly, and then ultrasonicate for 5 min to obtain a uniformly dispersed aqueous solution. ② Dissolve 1.236 g of 2-(perfluorooctyl)ethyl methacrylate, 6.493 g of ethylene glycol dimethacrylate, 1.000 g of methacrylic acid, and 0.070 g of azobisisobutyronitrile in 20 mL of chloroform, stir and mix well, and then ultrasonically treat for 5 min to obtain a uniformly dispersed oil phase solution; ③. Place the three-necked flask in step ① on a magnetic stirrer and stir at a speed of 1500 rpm, then slowly drip the oil phase solution obtained in step ② into the three-necked flask with a pipette, and continue emulsification for 10 min after the addition is completed to obtain a stable milky white oil-in-water emulsion; S12, the three-necked flask in step S1 was sealed with a rubber stopper, one end was connected to an oil seal, and the other end was connected to a nitrogen source, nitrogen was continuously introduced for 10 min, and then placed in a 70°C oil bath at a speed of 500 rpm for 10 h to obtain a polymer microsphere mixed solution; S13, recovering the polymer microspheres by centrifugation, washing them three times with deionized water, and then washing them three times with ethanol to obtain a product; then placing the washed microspheres in a vacuum drying oven, drying them at a constant temperature of 40°C for 24 hours, and cooling them to room temperature to obtain dry microspheres; S14: The dried microspheres were respectively subjected to solvent exchange with ethanol and ethyl acetate solutions and then dried to obtain a fluorine-containing polymer microsphere adsorbent material. The microspheres were then placed in a vacuum drying oven and dried at a constant temperature of 40°C for 24 h. The microspheres were cooled to room temperature to obtain a fluorine-containing polymer microsphere adsorbent material.

[0041] Figure 1 This is a scanning electron microscope image of the fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1. It can be seen from the figure that the adsorbent material is spherical (a). Due to the volatilization of the oil phase after polymerization, the surface and interior are porous structures (b), which can expose more adsorption sites and accelerate mass transfer.

[0042] Figure 2 The actual image of the emulsion in step S1 of the experiment (a) and the fluorescence microscope image of the emulsion droplets stained with Nile red (b) show that the water-in-oil emulsion presents a uniform milky white color, indicating that the emulsion system has a certain stability (a). Figure 2 As can be seen in (b), the emulsion droplets are relatively uniform in size and well dispersed.

[0043] Figure 3 This is the infrared spectrum of the fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1. -1 The characteristic peak at 1725 cm -1 The characteristic peak at 1245 cm -1 and 1147 cm -1 The two characteristic peaks at 1211 cm -1 and 1112 cm -1 They correspond to the asymmetric stretching vibration and symmetric contraction vibration of CF, respectively. This shows that the fluorine-containing polymer microsphere adsorbent material based on emulsion polymerization was successfully prepared.

[0044] Figure 4 This is the nitrogen adsorption-desorption curve of the fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1. It was detected that the adsorbent had a nitrogen adsorption capacity of 258.94 m 2 The higher specific surface area of ​​​​the adsorbent of 1.5447 W / g can prove the porous structure of the adsorbent, which can expose more adsorption sites.

[0045] The present invention also provides an application method of a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium, wherein the prepared fluorine-containing polymer microsphere adsorbent is added to lithium-containing wastewater to selectively adsorb lithium ions, and a constant temperature reaction is carried out under stirring conditions, thereby achieving specific targeted recognition and ultra-high capacity adsorption of lithium ions.

[0046] Specifically, the fluorinated polymer microsphere adsorbent material based on the emulsion polymerization method prepared in Experiment 1 was used to conduct an adsorption experiment on lithium ion aqueous solutions of different concentrations. The test method is as follows: (1) preparing lithium nitrate aqueous solutions with lithium concentrations of 10 mg / L, 20 mg / L, 50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, 350 mg / L, 400 mg / L, 450 mg / L, and 500 mg / L, respectively; taking 20 mL of each of these lithium-containing solutions of different concentrations and placing them in 10 50 mL conical flasks; (2) Weigh 20 mg of the fluorinated polymer microsphere adsorbent material based on the emulsion polymerization method prepared in Experiment 1, weigh a total of 10 portions, put them into 50 mL conical flasks containing lithium ion aqueous solutions of different concentrations, and put them into a constant temperature oscillator with parameters set at 25 °C, 180 rpm, and 24 h for adsorption experiment; (3) taking the solution before and after adsorption from the conical flask respectively, and measuring the lithium ion concentration in the solution using an atomic absorption spectrometer (AAS); Figure 5 The isothermal adsorption curve shows that the actual adsorption behavior of the adsorbent material for lithium ions is more consistent with the Langmuir model, indicating that the adsorption sites are evenly distributed and monolayer adsorption occurs. The fitting shows that the maximum adsorption capacity Qmax of the fluorinated polymer microsphere adsorbent material for lithium ions based on emulsion polymerization is 38.5 mg / g.

[0047] The fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1 was used to conduct a kinetic adsorption experiment on a lithium ion aqueous solution. The test method is as follows: (1) Prepare a lithium nitrate aqueous solution with a lithium concentration of 500 mg / L, and place 100 mL of the lithium-containing solution in a 250 mL beaker; (2) Weigh 100 mg of the fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1 and place it in a beaker of aqueous solution with a lithium concentration of 500 mg / L; stir with a magnetic stirrer at 500 rpm, a temperature of 25 °C, and a time of 180 min; (3) At the time of 0, 1, 3, 5, 10, 30, 60, 90, 150, and 180 min, 1 mL of the solution was taken from the beaker and the lithium ion concentration in the solution was measured using an atomic absorption spectrometer (AAS); Figure 6The kinetic adsorption curve shows that the adsorbent material reaches kinetic adsorption equilibrium in 60 min. The pseudo-second-order kinetic model is more consistent with the actual kinetic adsorption process, indicating that chemical adsorption plays a dominant role in the adsorption process between lithium ions and the adsorbent.

[0048] The adsorption selectivity of lithium ions in a monovalent metal mixed solution was analyzed using the fluorinated polymer microsphere adsorbent material based on the emulsion polymerization method prepared in Experiment 1. The test method is as follows: (1) Prepare a 20 mL mixed aqueous solution containing 40 mMol / L lithium ions, 40 mMol / L sodium ions, and 40 mMol / L potassium ions; place the mixed aqueous solution in a 50 mL conical flask; (2) Weigh 20 mg of the fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1, put it into a mixed aqueous solution containing 40 mMol / L lithium ions, 40 mMol / L sodium ions, and 40 mMol / L potassium ions, and place it in a constant temperature oscillator with the parameters set at 25 °C, 180 rpm, and 24 h for adsorption experiment; (3) taking the ion solution before and after adsorption in the conical flask, and using inductively coupled plasma mass spectrometry (ICP MS) to determine the concentrations of lithium ions, sodium ions, and potassium ions in the solution; Figure 7 The fluorinated polymer microsphere adsorbent material based on emulsion polymerization has the selective adsorption capacity for lithium ions in a monovalent metal mixed solution. It can be seen that the fluorinated polymer microsphere adsorbent material based on emulsion polymerization can separate lithium ions from a mixed solution containing sodium ions and potassium ions, indicating that the adsorbent material can also excellently complete the separation and recovery of lithium ions in a monovalent metal mixed solution containing sodium ions, potassium ions, etc. with a similar charge state to lithium ions.

[0049] The adsorption selectivity of lithium ions in a high-valent metal mixed solution was analyzed using the fluorinated polymer microsphere adsorbent material based on the emulsion polymerization method prepared in Experiment 1. The test method is as follows: (1) Prepare a mixed aqueous solution containing 40 mMol / L lithium ions, 40 mMol / L cobalt ions, and 40 mMol / L manganese ions in a volume of 20 mL; place the mixed aqueous solution in a 50 mL conical flask; (2) Weigh 20 mg of the fluorinated polymer microsphere adsorbent material prepared by emulsion polymerization in Experiment 1, put it into a mixed aqueous solution containing 40 mMol / L lithium ions, 40 mMol / L cobalt ions, and 40 mMol / L manganese ions, and place it in a constant temperature oscillator with the parameters set at 25 °C, 180 rpm, and 24 h for adsorption experiment; (3) taking the ion solution before and after adsorption in the conical flask, and using inductively coupled plasma mass spectrometry (ICP MS) to determine the concentrations of lithium ions, cobalt ions, and manganese ions in the solution; Figure 8 The fluorinated polymer microsphere adsorbent material based on emulsion polymerization has the selective adsorption ability for lithium ions in a mixed solution of high-valent metals. It can be seen that the fluorinated polymer microsphere adsorbent material based on emulsion polymerization can separate lithium ions from a mixed solution containing cobalt ions and manganese ions, indicating that the adsorbent material can excellently separate and recover lithium ions in a mixed solution containing high-valent metals such as cobalt ions and manganese ions.

[0050] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium, characterized in that: The fluorinated polymer microsphere adsorbent uses 2-(perfluorooctyl)ethyl methacrylate as a functional monomer and is prepared based on an emulsion polymerization method; the particle size of the fluorinated polymer microsphere adsorbent is 12-17 μm; the pore size of the fluorinated polymer microsphere adsorbent is 50-200 nm, and the specific surface area is 100-300 m² / g, so as to ensure that lithium ions can pass smoothly and combine with the adsorption sites.

2. A method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium, used for preparing the fluorinated polymer microsphere adsorbent according to claim 1, characterized in that: The following steps are included in the control: S1 determines the preparation method and sets initial parameters to carry out emulsion polymerization; S2 measured the pore size and specific surface area of ​​the microspheres; S3 adjusts a single parameter, conducts multiple experiments, and records the results of each experiment; S4 fits the empirical formula according to the experimental data and adjusts the parameters according to the fit; S5: repeat the above steps S1 to S4 until a satisfactory microporous structure is obtained to obtain a fluorine-containing polymer microsphere adsorbent.

3. The method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium according to claim 2, characterized in that: In step S1, the preparation method comprises the following steps: S11: adding an emulsifier to deionized water to obtain a uniformly dispersed aqueous solution; dissolving 2-(perfluorooctyl)ethyl methacrylate, ethylene glycol dimethacrylate, methacrylic acid, and azobisisobutyronitrile in chloroform to obtain a uniformly dispersed oil solution; slowly dropping the oil solution into the aqueous solution under high-speed stirring to form a stable milky white oil-in-water emulsion; S12: The three-necked flask in step S11 is sealed with a rubber stopper, one end is connected to an oil seal, and the other end is connected to a nitrogen source, and nitrogen is continuously introduced for 8-10 min, and then placed in an oil bath at 70-80 °C and reacted at a speed of 300-500 rpm for 10-12 h to obtain a polymer microsphere mixed solution; S13: After the reaction is completed, the polymer microspheres are recovered by centrifugation, washed with deionized water and ethanol for multiple times, and dried to obtain dry microspheres; S14: using ethanol and ethyl acetate solutions to perform solvent exchange on the dried microspheres respectively and then drying them to obtain a fluorine-containing polymer microsphere adsorbent material.

4. The method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium according to claim 3, characterized in that: In steps S13 and S14, the drying of the microspheres includes placing the microspheres in a vacuum drying oven, drying them at a constant temperature of 40 to 50° C. for 24 to 25 h, and cooling them to room temperature to obtain dried microspheres.

5. The method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium according to claim 3, characterized in that: Step S11 includes the following steps: S111: Add deionized water and emulsifier into a three-necked flask, stir and mix evenly, and then perform ultrasonic treatment for 3-5 min to obtain a uniformly dispersed aqueous solution; S112: 2-(Perfluorooctyl)ethyl methacrylate, ethylene glycol dimethacrylate, methacrylic acid, and azobisisobutyronitrile were dissolved in chloroform, stirred and mixed evenly, and then ultrasonically treated for 3 to 5 minutes to obtain a uniformly dispersed oil phase solution; S113: Place the three-necked flask in step S111 on a magnetic stirrer and stir at a speed of 1200-1500 rpm, then slowly drip the oil phase solution obtained in step S12 into the three-necked flask with a pipette, and continue emulsification for 8-10 minutes after the dripping is completed to obtain a stable milky white oil-in-water emulsion.

6. The method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium according to claim 5, characterized in that: The emulsifier is sodium dodecyl sulfate; the mass ratio of the emulsifier to deionized water is 1-2:800; the molar ratio of the 2-(perfluorooctyl)ethyl methacrylate, the ethylene glycol dimethacrylate and the methacrylic acid is 0.2-0.6:1.82-2.82:1; the amount of the methacrylic acid in the chloroform is 33.33-50 g / L; the amount of the azobisisobutyronitrile in the chloroform is 3.33-4 g / L; the volume ratio of the chloroform to deionized water is 1:2-3.

7. The method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium according to claim 3, characterized in that: In step S13, when washing the polymer microspheres, the amount of deionized water used is 33.33-40 g / L; the amount of ethanol used is 33.33-40 g / L.

8. The method for controlling the structure of a fluorinated polymer microsphere adsorbent for selectively adsorbing lithium according to claim 3, characterized in that: In step S5, steps S1 to S4 are repeated, the experimental parameters are gradually adjusted, verification experiments are performed, and the preparation process is iteratively optimized to obtain a fluorine-containing polymer microsphere adsorbent with a satisfactory microporous structure.

9. An application method of a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium, wherein the fluorine-containing polymer microsphere adsorbent prepared in claim 1 is added to lithium-containing wastewater to selectively adsorb lithium ions, characterized in that: By reacting at a constant temperature under stirring conditions, specific targeted recognition and ultra-high capacity adsorption of lithium ions can be achieved.

10. The method for applying a fluorine-containing polymer microsphere adsorbent for selectively adsorbing lithium according to claim 9, characterized in that: The amount of the fluorine-containing polymer microsphere adsorbent added to the wastewater is 0.1-2 g / L, the reaction temperature is 25° C., the reaction time is 24 h, and the stirring speed is 180 rpm.

Citation Information

Patent Citations

  • Materials used for extracting lithium from brine, and method

    CN103785358A

  • Cationic fluorine-containing fabric finishing agent and preparation method thereof

    CN108018718A

  • Hydrophobic and oleophobic fluorine-containing microsphere and preparation method thereof

    CN115010932A

  • Cationic amphiphilic fluorine-containing hydrogel adsorbent as well as preparation method and application thereof

    CN115475607A

  • Preparation method of temperature-sensitive fluorine-containing polymer microgel adsorbent

    CN118638264A

Cited By

  • Preparation and application method of porous microsphere adsorbent for extracting lithium

    CN120518815A

  • Preparation and application method of porous microsphere adsorbent for lithium extraction

    CN120518815B

  • Preparation method and application of fluorine-containing copolymer adsorbent for high-selectivity lithium extraction

    CN120733711A

  • Preparation method of high-selectivity lithium ion adsorbent

    CN121198264A